2023
DOI: 10.3390/jcm12185895
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Predictors for Functional Outcome and Complication Rate in Total Hip Arthroplasty through Minimally Invasive and Conventional Approaches: A Systematic Review and Meta-Regression Analysis of 41 Randomized Controlled Trials

Nikolai Ramadanov,
Marko Ostojic,
Philip Lazaru
et al.

Abstract: Objective: To investigate and identify risk factors and predictors for the difference in functional outcome and complications between total hip arthroplasty (THA) through minimally invasive and conventional approaches, using a meta-regression analysis of randomized controlled trials (RCTs). Methods: A systematic review of the literature up to 31 July 2022 was performed. A meta-regression was conducted based on a random effects meta-analysis using the Hartung–Knapp–Sidik–Jonkman method. Results: A total of 41 R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 62 publications
(439 reference statements)
3
5
0
Order By: Relevance
“…In our patient cohort, the mean incision length for SuperPATH HA was 6.89 cm, ranging from 6.90 to 7.82 cm, and the mean incision length for CA HA was 11.19 cm, ranging from 9.08 to 17.1 cm. This finding is consistent with the recent metaregression analysis 13 investigating predictors of outcome for minimally invasive THA and CA THA. There, the effect size of HHS ≥6 months postoperatively decreased by an average of 0.82 points for each 1 cm increase in mean incision length.…”
Section: Patient-related Predictors Of Hhs ≤1 Week Postoperativelysupporting
confidence: 92%
See 4 more Smart Citations
“…In our patient cohort, the mean incision length for SuperPATH HA was 6.89 cm, ranging from 6.90 to 7.82 cm, and the mean incision length for CA HA was 11.19 cm, ranging from 9.08 to 17.1 cm. This finding is consistent with the recent metaregression analysis 13 investigating predictors of outcome for minimally invasive THA and CA THA. There, the effect size of HHS ≥6 months postoperatively decreased by an average of 0.82 points for each 1 cm increase in mean incision length.…”
Section: Patient-related Predictors Of Hhs ≤1 Week Postoperativelysupporting
confidence: 92%
“…Elderly patients appear to benefit more from SuperPATH HA than from CA HA compared with younger patients. This finding is consistent with the results of a recent meta-regression analysis 13 investigating predictors of minimally invasive THA outcome and CA THA outcome. This study 13 also found a strong positive association between patient age and the effect size of HHS ≤3 months postoperatively.…”
Section: Patient-related Predictors Of Hhs ≤1 Week Postoperativelysupporting
confidence: 92%
See 3 more Smart Citations